MEREDAM RASA INSECURITY DALAM KARYA POTRAIT FOTOGRAFI BERJUDUL CANTIK TIDAK HANYA DARI FISIK - Perdana, Ahmad Zakhi Danang; Endriawan, Didit; Kusumanugraha, Sigit (Telkom University, 2023)
Insecure is a feeling of insecurity where an individual feels insecure and anxious about something. At this time people often mention the word insecure when they see someone more beautiful than themselves. everyone who has feelings of insecurity can vary. The causes of insecurity can come from events that cause trauma, past experiences, social conditions, to the surrounding environment. Insecurity is a condition that should not be ignored, because it can be related to the condition of the body as a whole, it can even reduce a person's quality of life. Therefore, the author would like to convey in the work of the Final Project that beauty is not only from the physical in the form of the work. Therefore, the author made a work entitled